Non-Fregean Logics of Analytic Equivalence (II) - Biłat, Andrzej (Bulletin of the Section of Logic, 2015)
This paper presents the main assumptions of Andrzej Grzegorczyk’s last research project concerning the logic of synonymity. It shows that the basis of logic of analytic equivalence, presented in the first part of the work, fully corresponds with these assumptions.